In situ synthesis of nanoclay filled polyethylene using polymer supported metallocene catalyst system - Z. V. P Murthy; Parimal A Parikh; Smitha Rajesh (Química Nova, 2011)
In situ ethylene polymerizations were performed using bis(cyclopentadiene)titanium dichloride supported on polyethersulfone as catalyst. The bis(cyclopentadiene)titanium dichloride supported on polyethersulfone catalyst activity estimated by ethylene polymerization was 360 kgPE/molTi/h. During polymerization the fillers used were montmorillionite nanoclays having surface modifications with 35-45 wt% dimethyl dialkyl(14-18)amine (FA) and 25-30 wt% trimethyl stearyl ammonium (FB). These fillers were pretreated with methylaluminoxine (MAO; cocatalyst) for better dispersion onto the polymer matrix. The formation of polyethylene within the whole matrix was confirmed by FTIR studies. It was found that the nature of nanofiller did not have any remarkable effect on the melting characteristics of the polymer. TGA study indicates that nanoclay FB filled polyethylene has higher thermal stability than nanoclay FA filled polyethylene. The melting temperature of the obtained polyethylenes was 142 ºC, which corresponds to that synthesized by the polyether sulfone supported catalyst.